THE EFFECT OF ONLINE ADVERTISING ON CONSUMER BUYING INTEREST IN ONLINE SELLING APPLICATIONS WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE (Study From Member of United Kingdom Medical Doctor Department) - Ian Wooton; Zhenyu Cui (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2022)
The results of this study show. (1) It can be seen that the value of the adjusted R square is 0.758 or 75.8%. This shows that consumer satisfaction (Y1) and advertising (X) can explain purchase intention (Y2) of 75.8%, the remaining 24.2% (100% - 75.8%) is explained by other variables outside the research model. This. Such as service, price and interest in buying. (2) The results of the (Partial) t test show that tcount (7.413) > ttable (1.685), likewise with a significance value of 0.00 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the advertising variable(X) positive and significant effecton consumer satisfaction (Y1).(3) The results of the t test (Partial) can be seen that the value of tcount (3.059) > ttable (1.685), and the significance value is 0.00 <0.05, it can be concluded that the second hypothesis is accepted, meaningadvertisement(X) positive and significant effecton buying interest (Y2). (4) The results of the path analysis test show that the direct effect of variable X on variable Y2 is 0.377. While the indirect effect through the Y1 variable is 0.769 x 0.554 = 0.426, the calculation results obtained show that the indirect effect through the Y1 variable is greater than the direct effect on the Y2 variable.